Evaluation of omega-3 enrichment in commercial feed for gourami (Osphronemus gouramy L.) fingerlings - Tambunan, Fitri Rahmayani; Aryani, Netti; Heltonika, Benny (Universitas Malikussaleh, 2025)
Gourami (Osphronemus gouramy L, 1801) is one of the freshwater fish commodities with high economic value that has slow growth. The feed used is still very minimal so the growth rate of gourami fish is slow. One approach that can be taken to increase the growth and nutritional value of gourami fish is by adding nutrients in the form of omega-3 salmon fish oil to the feed. This study aimed to evaluate the enrichment of commercial feed with omega-3 in increasing the growth and nutritional value of gourami fish carcasses. This study was carried out from May to July 2023 at the Laboratory of Marine Microbiology, Faculty of Fisheries and Marine, University of Riau. This study used a completely randomized design (CRD) experimental method with 4 experiments and 3 replications, the experiments used were, P0 (without fish oil), P1 (salmon oil 5g/kg), P2 (salmon oil 10g/kg), P3 (salmon oil 15 g/kg). The fingerlings were raised for 60 days with a stocking density of 20 fish/container. The results showed that enrichment of feed with salmon fish oil significantly effect (P<0.05) on growth rate and increased nutritional value. Experiment P3 (salmon oil 15g/kg) produced a higher growth rate compared to other treatments, namely absolute weight of 9.05+0,76 g, absolute length of 4.80 cm, specific growth rate of 1.16+0,07 %, feed conversion ratio of 2.4+0,24%, efficiency feed of 40.5+4,0%, hepatosomatic index of 3.3+0,11%, viscera somatic index of 3.6+0,22%, mesenteric fat index of 3.2+0,06%, EPA of 2.85%, and DHA of 2.31%. In conclusion, adding salmon fish oil increases the growth and value of EPA and DHA in gourami fish meat. Water quality parameters were considered good with a temperature of 28-32oC, pH of 5.2-6.7, DO of 6.5-8.5 mg/l, and NH3 of 0.14-0.85 mg/l.Keywords: Feed Enrichment; Gourami Fingerlings; Growth; Nutritional Value